Analysis and Design of a steel cold storage hangar according to Eurocode 03 - Seghier, Ibtissam; Bahaz, Abdesselam, Directeur de thèse (My University, 2024)
This master thesis consists of analyzing and designing a steel cold storage hangar located in the province of ADRAR in accordance with the Eurocode 03 standard. This study is carried out in several stages. Firstly, an assessment of the loads and overloads and the effects of climatic conditions (wind and sand) is carried out according to the Algerian regulation RNV2013. Then, the different structural elements are dimensioned, followed by studying the connections according to Eurocode 03. Finally, the infrastructure study is carried out according to CBA 93. The Autodesk Robot Structural Analysis Professional software was used for this study.
Laghouat : Université Amar Telidji - Département de génie civil, Option: Structures .